Characterization of iron metabolism and erythropoiesis in erythrocyte membrane defects and thalassemia traits - Sulovská, Lucie; Holub, Dušan; Židová, Zuzana; Divoká, Martina; Hajdúch, Marián; Mihál, Vladimír; Vrbková, J; Horváthová, Monika; Pospíšilová, Dagmar (Biomedical papers of the Medical Faculty of the University Palacký, Olomouc Czech Republic, 2016)
BACKGROUND AND AIMS: Erythropoiesis is closely related to iron metabolism in a balanced homeostasis. Analyses of diverse erythroid and iron metabolism disorders have shown that disrupted erythropoiesis negatively affects iron homeostasis and vice versa. The aim of this study was to characterize the relationship between erythropoietic activity and iron homeostasis in pediatric patients with erythrocyte membrane defects and thalassemia traits. METHODS: Selected markers of erythropoietic activity (erythropoietin, soluble transferrin receptor - sTfR and growth differentiation factor 15) and iron status parameters (serum iron, ferritin and hepcidin) were evaluated in pediatric patients with erythrocyte membrane defects and thalassemia traits. RESULTS: The patients with erythrocyte membrane defects and thalassemia traits had altered iron homeostasis due to disturbed erythropoiesis. In comparison with healthy controls, they had a normal to low hepcidin/ferritin ratio and concomitantly elevated sTfR. CONCLUSION: The findings suggest that pediatric patients with erythrocyte membrane defects and thalassemia traits are more susceptible to iron overload than the general population and that the (hepcidin/ferritin)/sTfR ratio can be used to monitor any worsening of the disease.
Keywords: železo; hemostáza; erytropoéza; talasemie; dědičná eliptocytóza; Humans; Iron; Elliptocytosis, Hereditary; dítě; Child; analýza rozptylu; hepcidiny; Analysis of Variance; Erythrocyte Membrane; Thalassemia; lidé; Hepcidins; Erythropoiesis; předškolní dítě; dědičná sférocytóza; Hemostasis; erytrocytární membrána; Adolescent; Spherocytosis, Hereditary; Child, Preschool; mladiství